2018
DOI: 10.1155/2018/3010898
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms ofIL1B, IL6,andTNFαin a Chinese Han Population with Pulmonary Tuberculosis

Abstract: Background The factors that predispose to pulmonary tuberculosis (PTB) are not fully understood. Previous studies have shown that cytokine gene polymorphisms were associated with PTB. Objectives In this study, we have investigated the relationship between ILB, IL6, and TNFα polymorphisms and a predisposition to Mycobacterium tuberculosis (MTB) infection and PTB. Methods A total of 209 cases of PTB, 201 subjects with latent TB infection (LTBI), and 204 healthy controls (HCS) were included in this study. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…In this current study showed that no association between genotypes and alleles of IL1β+3954 C/T, IL18-137 G/C, and IL18-607 C/A gene polymorphism with T2DM-TB compared to control group and T2DM-TB compared to T2DM group. The association of IL1β+3954 C/T gene polymorphism with TB and latent TB has been reported in the literature before, with a different result [9], [18], [19], [20], but the associations of IL1β+3954 C/T gene polymorphism with T2DM-TB have not reported.…”
Section: Discussionmentioning
confidence: 84%
“…In this current study showed that no association between genotypes and alleles of IL1β+3954 C/T, IL18-137 G/C, and IL18-607 C/A gene polymorphism with T2DM-TB compared to control group and T2DM-TB compared to T2DM group. The association of IL1β+3954 C/T gene polymorphism with TB and latent TB has been reported in the literature before, with a different result [9], [18], [19], [20], but the associations of IL1β+3954 C/T gene polymorphism with T2DM-TB have not reported.…”
Section: Discussionmentioning
confidence: 84%
“…Multivariable logistic analysis revealed the association between rs7453920 GA genotype and an increased risk of TB. As mentioned in the literature, GA genotype of SNP rs2069837 A>G located within IL‐6 was associated with PTB, while GG genotype did not show any association with TB (Wu et al, ). Prior studies have noted the relationship between CT genotype of TNF‐857 and spinal TB, while TT genotype did not correlate with spinal TB (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Another study showed that A allele of TNF-α at position (-308) was associated with tuberculosis infection [12]. Wu et al, (2017) notice that TNF-α gene polymorphism (-308G/A) was associated with severity of tuberculosis infection in a Chinese Han Population [23]. In this context, previous study showed that the GG wild type genotype significantly decreased in diabetic patients and also in tuberculosis patients compared to healthy subjects, different with our study that found the GG genotype frequency was highest in all groups.…”
Section: Discussionmentioning
confidence: 99%